Global prevalence of constipation during pregnancy: a systematic review and meta-analysis - Salari, Nader; Mohamadi, Sakine; Hemmati, Mahvan; Fallahi, Amirreza; Rasoulpoor, Shabnam; Zarei, Hosna; Shohaimi, Shamarina; Mohammadi, Masoud (BioMed Central, 2024)
Background: Constipation is a common complication and an unpleasant experience during pregnancy. Due to hormonal factors, intestinal movements decrease during this time, causing the digestive system to malfunction. This study aims to explore the worldwide prevalence of constipation during pregnancy to prevent and minimize its complications. Method: Researchers conducted a meta-analysis of published data on the prevalence of constipation in pregnancy. The articles, which covered the period 1966 to 2024, were collected by searching Embase, PubMed, Scopus, Science Direct, Wos, and the Google Scholar search engine. The initial search was conducted on July 21, 2024, and the final update was made on August 10, 2024. Results: Thirteen studies were identified to determine the prevalence of constipation during pregnancy. The results show that the global prevalence of constipation throughout pregnancy is 32.4%, with the first trimester at 21.1%, the second trimester at 34%, and the third trimester at 30.3%. Conclusion: According to a study, constipation is most common during the second trimester of pregnancy and the least common during the first trimester. Further research on the causes of constipation and prevention methods can help decrease its prevalence during pregnancy. Therefore, it is important to provide educational interventions on nutrition and encourage moderate physical activity during pregnancy to reduce the occurrence of constipation.